Awareness and Utilization of ICT-Based Resources among Medicals Profes sionals of IGIMS, Patna (LIS TODAY, 2025)
The use of Information and Communication Technology or ICT is important in reforming  or modernizing medical education and the healthcare system. The present study investigates  the use of ICT tools by students, faculty and researchers at Indira Gandhi Institute of  Medical Sciences (IGIMS), Patna. A total of 80 people were surveyed through a structured  questionnaire, of which 65 valid responses were used for the analysis. It aimed to measure  ICT use, frequency of use, awareness, and specific usage in the academic-clinical setting. The Results show a high percentage of use of ICT for academic learning, research,  references for clinical practice and online resources. Nonetheless, the paper reveals  that there is also little familiarity with more sophisticated ICT tools from an awareness  perspective, lack of experience with user education workshops, and infrastructural and  accessibility issues. But, in spite of these challenges there was significant receptivity  towards the use of institutional repositories, medical databases, and ICT-based education  among respondents. The findings provided perspectives on ICT’s increasing role in  medical education and the need for digital skills to be dynamic. It also suggests better  ICT training on a regular basis, a better infrastructure for ICT and awareness raising in  order to make optimal use of online resources. This must be done to better use ICT in  IGIMS, Patna for academic and clinical learning.
Keywords: ICT; E-Resources; Medical Library; Medical Institutional Repository; Medical Database; User Awareness; IGIMS Patna